Alstroemeria (Alstroemeriaceae) in the caatinga of Brazil, with a new species - Assis, Marta C.; Mello-Silva, Renato (Phytotaxa, 2016)
Five species of Alstroemeria from caatinga in Brazil are presented. Three of them are endemic to this vegetation, including a new species, A. stramonia, here described. We provide descriptions, illustrations, comments, and a key to the species.